How does boron modify the growth of Crotalaria juncea? A legume with phytostabilizing potential - de Mendonça, Gabriel Wanderley [UNESP]; Aguilar, Jailson Vieira [UNESP]; de Marcos Lapaz, Allan [UNESP]; da Silva de Paiva, Wesller [UNESP]; Ferreira, Tassia Caroline [UNESP]; Souza, Lucas Anjos; Justino, Gilberto Costa; de Camargos, Liliane Santos [UNESP] (Taylor & Francis, 2023)
Soil contamination by boron (B) occurs in different ways, such as through mineral fertilisers and irrigation, and in surface waters it has increased significantly over the years. It is an important element for plants, participating in several physiological processes. This work aimed to evaluate the behaviour of Crotalaria juncea, widely used as green manure. The species that tolerates B up to a dose of 60 mg dm−3 has the capacity to phytoremediate B and is classified as a phytostabilizer. It is clear that a dose of 120 mg dm−3 of B is harmful to the growth of the species.
Keywords: ecophysiology; micronutrient; N metabolism; Phytoremediation